Productivity and nutritional value of barley and wheat forage from Colombian’s highlands - Mancipe-Muñoz, Edgar A.; Vásquez-Venegas, Julio E.; Castillo-Sierra, Javier; Ortiz-Cuadros, Ronnal E.; Avellaneda-Avellaneda, Yesid; Vargas-Martínes, Juan de Jesús (Agronomía Mesoamericana, 2021)
Introduction. The evaluation and selection of small grain crops for ruminant production systems promote efficient systems. However, it is necessary to evaluate the diversity present in national germplasm banks to recognize accessions with outstanding attributes. Objective. To evaluate the agronomic and nutritional response of accessions of small grain forage crops. Materials and methods. Between June and December 2018 26 accessions of barley (Hordeum vulgare) and 25 accessions of wheat (Triticum sp.) were established at the Tibaitatá research center of Corporación Colombiana de Investigación Agropecuaria (AGROSAVIA), Mosquera, Colombia. Four repetitions of each material were planted in rows of 5,0 m to 0.2 m between plants. During the phenological period of the crop, height, vigor, presence of pests and diseases, number of stems per plant and leaves per plant were evaluated fortnightly. Once 50 % of the plants of each variety reached the states of thickened pod or milky-pasty grain, two plants were harvested per row, and steam, leaves, and spike proportions, dry matter production, and nutrients concentration were determined. The variables evaluated fortnightly were analyzed with a block model with repeated measures, while the others were analyzed with a random block model. Results. The older the crop the higher the height of the plant, relation stem: plant, disease presence, and less vigor were presented. During the thickened pod stage, the C7 and T24 accessions had the highest (p<0.05) biomass production, while in the milky-pasty stage it was the T24 accession (p<0.05). Conclusión.Barleys C7, C17 and C20, and wheat T12, T15 and T24 showed productive and compositional characteristics with the potential to continue being evaluated in future research works.